Diagnóstico de boas práticas de alimentação em domicílios da cidade de Santa Maria - RS - Deon, Barbara Cecconi (2012)
The World Health Organization estimates that the diseases caused by contaminated food constitute one of the most widespread sanitary problems. Currently, the food prepared at home have had great influence on the ocurrence of outbreaks of Diseases Transmitted by Food (DTFs), as a result of hygienic failures in the manipulation of foods. Taking this situation into account, this work aimed to develop and apply an education program on good practice for the manipulation of foods at home. The present study was conducted in 615 houses distributed in the 8 Administrative Regions (AR) of the city of Santa Maria RS, between March and November 2011. In order to make the diagnosis, the person in charge of the manipulation of foods at home was asked to complete a form covering personal data, knowledge and practice of food safety. Also, a List of Evaluation of Good Practice at Home (LEGPH) was applied to identify the level of hygienic and sanitary conditions in home kitchens. After the diagnosis, an education program was developed using the most popular means of communication reported by the population for a further reapplication of the LEGPH in a third of the sample of homes with the aim of evaluating the efficiency of this program. Through the application of the form, it was found that the urban central region differed in most cases from the north, south, central-west and western regions. The level of education of the interviewees influenced on the classification of the houses, that is, the higher the level of education, the higher the level of adequacy. After the education program, it was verified that there was no significant difference in the level of adequacy of the houses when compared to the first application, however, an enhancement was observed in almost all of the items of the LEGPH. Since it is difficult to modify practices and habits of the population with only three months of educational actions, it is suggested the need to continue with programs on the consciousness-raising process of the population due to the risks related to food manipulation, seeking a food safety perspective and an improvement of the quality of life of the population.